2016
DOI: 10.1007/s00018-016-2213-2
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative SNARE peptides stabilize the fusion pore in a narrow, release-unproductive state

Abstract: Key support for vesicle-based release of gliotransmitters comes from studies of transgenic mice with astrocyte-specific expression of a dominant-negative domain of synaptobrevin 2 protein (dnSNARE). To determine how this peptide affects exocytosis, we used super-resolution stimulated emission depletion microscopy and structured illumination microscopy to study the anatomy of single vesicles in astrocytes. Smaller vesicles contained amino acid and peptidergic transmitters and larger vesicles contained ATP. Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 57 publications
15
72
0
Order By: Relevance
“…Astrocytes, like other eukaryotic cells, contain secretory vesicles with varied diameter and are suitable for vesicle luminal cargo release, as for the delivery of membrane-associated receptors to the plasma membrane. [45][46][47][48] Compared with neurons, the kinetics of exocytosis was shown to be slower in astrocytes 49 with several types of discrete vesicle interactions with the plasma membrane 24,50 as recorded in this study. The interaction of NPs with the plasma membrane and especially how NPs modify merging of the unitary vesicle with the plasma membrane have not been carried out but are important in relation to intracellular retention and possible clearance of NPs.…”
Section: Discussionmentioning
confidence: 92%
“…Astrocytes, like other eukaryotic cells, contain secretory vesicles with varied diameter and are suitable for vesicle luminal cargo release, as for the delivery of membrane-associated receptors to the plasma membrane. [45][46][47][48] Compared with neurons, the kinetics of exocytosis was shown to be slower in astrocytes 49 with several types of discrete vesicle interactions with the plasma membrane 24,50 as recorded in this study. The interaction of NPs with the plasma membrane and especially how NPs modify merging of the unitary vesicle with the plasma membrane have not been carried out but are important in relation to intracellular retention and possible clearance of NPs.…”
Section: Discussionmentioning
confidence: 92%
“…The paradigm of gliotransmission being present in vivo , critically depends on experiments in mice expressing the dnSNARE peptide. However, the mechanism of action of this peptide was only recently described [8]. In contrast to the previously considered mechanism, where the dnSNARE peptide interferes exclusively at the stage of the formation of the SNARE complex between the vesicles and the plasmalemma, the results revealed that the dnSNARE peptides strongly affect the properties of the fusion pore after the vesicle membrane merges with the plasmalemma.…”
mentioning
confidence: 79%
“…Therefore, fusing vesicles remain connected to the plasma membrane with a narrow pore until the addition of new proteins and lipids to the fusion machinery reverses the process. Indeed, a variety of proteins, such as dynamin (Anantharam et al, 2011; Jackson et al, 2015), myosin II, actin (Aoki et al, 2010), SNARE proteins (Fang et al, 2008; Gucek et al, 2016), synaptotagmin (Wang et al, 2001; Lai et al, 2013), and complexin (Dhara et al, 2014) have been found to affect the fusion pore dynamics in chromaffin and PC12 cells. These studies highlight an active role of these components in impacting the fusion pore.…”
Section: Exocytosis In Excitable Cellsmentioning
confidence: 99%